The individual and collective effect of U.S colonialism in Puerto Rico: A scale constructiona and validation, whith implications for social work education and practice - Martínez Avilés, María de Lourdes (2011)
Understanding the individual and collective psychology of the people of Puerto Rico requiris an understanding of both the history of its colonialism and the U.S